Knowledge Management Village Devices In Ponorogo District, Does It Affect The Capability of Innovation? - Afifah, Izzatul; Sumarsono, Hadi; Wijianto, Wijianto (PERWIRA - Jurnal Pendidikan Kewirausahaan Indonesia, 2024)
This research aims to measure the influence of knowledge capture and knowledge acquisition on knowledge dissemination and the innovation ability of village heads in Ponorogo Regency, as well as assessing the role of knowledge dissemination as a mediator. This research method is quantitative, with data collection techniques through observation, questionnaires, and interviews. The research results show that knowledge capture has a significant effect on the dissemination of knowledge and innovation capabilities of village heads. Knowledge acquisition also has a significant effect on the dissemination of knowledge and innovation capabilities of village heads. Knowledge dissemination has been proven to have a significant effect on the innovation ability of village heads. In addition, knowledge dissemination also acts as a significant mediator in the relationship between knowledge capture and knowledge acquisition on innovation capabilities. This research confirms the importance of knowledge capture and knowledge acquisition in increasing dissemination and innovation at the village level.